Scanning electron microscopic analysis of the effect of Carisolv TM gel on periodontally compromised human root surfaces - Grisi, Daniela Corrêa [UNESP]; Theodoro, Letícia Helena [UNESP]; Sampaio, José Eduardo César [UNESP]; Grisi, Márcio Fernando de Moraes; Salvador, Sérgio Luiz de Souza (FapUNIFESP (SciELO), 2006)
The aim of this study was to analyze, under scanning electron microscopy (SEM), the morphologic characteristics of root surfaces after application of CarisolvTM gel in association with scaling and root planing (SRP). Sixty periodontally compromised extracted human teeth were randomly assigned to 6 groups: 1) SRP alone; 2) passive topical application of CarisolvTM + SRP; 3) active topical application of CarisolvTM + SRP; 4) multiple applications of CarisolvTM + SRP; 5) SRP + 24% EDTA; 6) topical application of CarisolvTM + SRP + 24% EDTA. CarisolvTM gel was applied to root surfaces for 30 s, followed by scaling and root planing, consisting of 50 strokes with Gracey curettes in an apical-coronal direction, parallel to the long axis of the tooth. The only exception was group 4, in which the roots were instrumented until a smooth, hard and glass-like surface was achieved. All specimens were further analyzed by SEM. The results showed that the treatment with CarisolvTM caused significant changes in root surface morphology of periodontally compromised teeth only when the chemical agent was actively applied (burnishing technique). CarisolvTM failed to remove the smear layer completely, especially with a single application, independently of the method of application. Multiple applications of CarisolvTM were necessary to achieve a smear layer reduction comparable to that obtained with 24% EDTA conditioning.
Keywords: CarisolvTM; Periodontal disease; Scaling and root planning; Scanning electron microscopy; Carisolv; glutamic acid; leucine; lysine; analysis of variance; clinical trial; controlled clinical trial; controlled study; dental surgery; drug effect; human; preventive dentistry; randomized controlled trial; scanning electron microscopy; surface property; tooth root; ultrastructure; Analysis of Variance; Dental Scaling; Glutamic Acid; Humans; Leucine; Lysine; Microscopy, Electron, Scanning; Root Planing; Smear Layer; Surface Properties; Tooth Root